Self Assessment and Review Microbiology Immunology - Jain Anshul, Chaurasia Rachna; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2009)
This book Self Assessment and Review Microbiology and Immunology provides important points of each topic in continuous manner not in parts as given in previous guides. This book consists of theory of each topic followed by its questions so theory portion helps you to solve new questions. This pattern of book allows you to revise whole infectious disease very clearly and quickly. This book provides sufficient matter which can be revised without any problem. Read the theory first then do questions. You realize that this way of learning makes topic easy to understand and easy to grasp for long-term memory. Try to complete each topic in one sitting. In the last we would like to say all the best for your PGMEE preparation and hope you will work hard with positive attitude in your mind.
Keywords: MCQs and Self-assessment,Microbiology and Immunology; Electronic books